Molecular characterization and in vitro functional analysis of putative immunoprotective molecules in the soft tick, Ornithodoros savignyi - Gaspar, A.R.M. (Anabella Regina Marques) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.